Efecto de la criomaceración de la flor de Jamaica (Hibiscus Sabdariffa) y guayaba (Ppsidium Guajava) en el color de una bebida Alcohólica en el espacio cie l*a*b - Aguirre Moreno, Sandy Enid (2021)
Cryomaceration is a technique used to improve sensometric characters after the grape harvest, prior to fermentation of the must to obtain white and red wines; but it is little used in other types of non-distilled alcoholic beverages. We sought to evaluate the effect of cryomaceration of Hibiscus sabdariffa and Psidium guajava on the color through the cielab space of an alcoholic beverage. An augmented factorial experiment (A*B + 3) with arrangement (2x3) with 6 treatments, 3 replicates with comparison pattern was applied. Chopped guava fruit (280 g/L), chopped fresh Jamaican flower (38.67 g/L) and the mixture of guava (140 g/L) with Jamaican flower (20 g/L) were added to 60 ºGL ethyl alcohol, cryomacerate at 5 ºC for 96 and 144 hours, after which the samples were heated to 64.7 ºC for 5 minutes, sieved, diluted to 12 ºGL and packaged in clear glass. For color analysis, a lutron RGB-1002 colorimeter was used, giving RGB values, which were converted to L*a*b* and then to luminosity, purity and hue; physicalchemical, sensory and polyphenol analysis (to the best treatment) was also performed. The results were analyzed statistically with Friedman and Holm's nonparametric test, reaching the conclusion that the best combination of treatments was the combination a1b1 (guava cryomacerate for 144 hours at 5 ºC), the indicators were: luminosity (34.73), tone (hab*)(31.56) and purity (C*) (30.37), 167.63 mg gallic acid/L. Keywords: Tonality, purity, luminosity, liquor, redistillation, polyphenols.